Contents of the Fiqh of Worship in Sharia Banking Studies at the Nahdlatul Ulama College of Sharia Economics (STIESNU) Bengkulu - M. Ngali Mubarok (Jurnal Aghniya, 2025)
Background: Islamic banking is growing rapidly but is still plagued by criticism of sharia compliance. Meanwhile, fiqh of worship teaches hablum minallah (the principle of unity in God), which is the spiritual basis of Islamic law. Method: Qualitative-descriptive, analyzing the RPS, teaching materials, and curriculum of fiqh of worship in the Islamic Banking Study Program at STIESNU Bengkulu through document study and content analysis. Results: Nine topics of fiqh of worship (definition, taharah, prayer, fasting, zakat, hajj/umrah, qurban/aqiqah, tahlil/talqin, marhaban/diba) are presented. This material contains values ​​of justice, transactional purity, and spiritual awareness that are relevant to sharia principles, but some have not been explicitly integrated into banking practices. Conclusion: Fiqh of worship can shape the integrity and morals of Islamic banking practitioners. Curriculum enrichment and spiritual deepening need to be carried out so that graduates have technical competence as well as Islamic morals in realizing a sharia financial system that is rahmatan lil ‘ālamīn.